Dolutegravir as First- or Second-Line Treatment for HIV-1 Infection in Children - Turkova, Anna; White, Ellen; Mujuru, Hilda A; Kekitiinwa, Adeodata R; Kityo, Cissy M; Violari, Avy; Lugemwa, Abbas; Cressey, Tim R; Musoke, Philippa; Variava, Ebrahim; Cotton, Mark F; Archary, Moherndran; et al. (The New England journal of medicine, 2021)
In an open-label, randomized, noninferiority trial, dolutegravir-based antiretroviral therapy was compared with standard care in children and adolescents starting first- or second-line therapy for HIV type 1 infection. Dolutegravir-based ART was superior to standard-care ART.